Spiritualitas Merti Desa dalam Pembangunan di Desa Mangunrejo, Magelang, Jawa Tengah - Siswayanti, Novita (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
Spirituality for Javanese people is considered as a lantern that provides light for human life to achieve goals. Spirituality like this can be found in the Merti Desa tradition as a form of implementing a culture of balance and harmony both vertically to God and horizontally to fellow humans and the environment. This study aims to determine the values ​​of spirituality and its preservation in the tradition of